2009
DOI: 10.1128/jb.01831-08
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Resistant Agglutinin 1 Is an Accessory EnteroaggregativeEscherichia coliColonization Factor

Abstract: Enteroaggregative Escherichia coli (EAEC) is an important cause of acute and persistent diarrhea. The defining stacked brick adherence pattern of Peruvian EAEC isolate 042 has previously been attributed to aggregative adherence fimbriae II (AAF/II), which confer aggregative adherence on laboratory E. coli strains. EAEC strains also show exceptional autoaggregation and biofilm formation, other phenotypes that have hitherto been ascribed to AAF/II. We report that EAEC 042 carries the heat-resistant agglutinin (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
72
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 55 publications
0
72
0
Order By: Relevance
“…Recent research is beginning to uncover chromosomal loci with promise as epidemiological and virulence markers [217][218][219][220][221].…”
Section: Enteroaggregative E Colimentioning
confidence: 99%
“…Recent research is beginning to uncover chromosomal loci with promise as epidemiological and virulence markers [217][218][219][220][221].…”
Section: Enteroaggregative E Colimentioning
confidence: 99%
“…To date, most studies of EAEC adherence have focused on structural adhesins known as aggregative adherence fimbriae. However, recent research has shown that EAEC strains also harbor an expanding repertoire of nonstructural outer membrane proteins that contribute to colonization (1,4,14,28).One such outer membrane protein is heat-resistant agglutinin 1 (Hra1), an accessory adhesin that we recently characterized in EAEC strain 042 (1). The hra1 gene (along with its 90% identical allelic variant hek, reported from uropathogenic E. coli and neonatal meningitic E. coli [11,39]) is predicted to encode a 29-kDa precursor, which is processed to a 25-kDa outer membrane protein.…”
mentioning
confidence: 99%
“…To date, most studies of EAEC adherence have focused on structural adhesins known as aggregative adherence fimbriae. However, recent research has shown that EAEC strains also harbor an expanding repertoire of nonstructural outer membrane proteins that contribute to colonization (1,4,14,28).…”
mentioning
confidence: 99%
See 2 more Smart Citations